UPAYA MENGATASI KEJENUHAN LATIHAN RENANG PRESTASI PADA PENDIDIKAN ATLET PERKUMPULAN RENANG YUSO YOGYAKARTA - Imawati, Intan (Jurnal Ilmiah Bina Edukasi, 2017)
This research was intended to know how to settle a boring in achievement swimming practice of swimming club athlete YUSO Yogyakarta. This research was descriptive research and used survey method. Understanding the sample by using population sampling, the samples that used from swimming club athlete Yuso Yogyakarta KU II and KU III were 20 athletes. Acquiring the data used questionnaire. The result shown that the effort to settle a boring in achievement swimming practice of swimming club athlete Yuso Yogyakarta was about 81,73%. Effort to settle a boring included intrinsic factor about 95,46%, extrinsic factor about 57,22%, age factor about 78,00%, and gender factor was about 96,25%. Referring to the average score that achieved, 81,73% was in 76% - 100%. So, it can be concluded that the effort to settle a boring in achievement swimming practice of swimming club athlete Yuso Yogyakarta was very positive.